(untitled) (Comprehensive Journal of Science, 2025)
The Thirty Years’ War (1618–1648 AD) is one of the bloodiest and most difficult wars in European history. Due to the Protestant Reformation in the 16th century, it began as a theological conflict between Catholics and Protestants, but it quickly developed into a comprehensive political conflict involving all major European powers. A Protestant uprising against Catholic authority in Bohemia led to a widespread religious conflict and the outbreak of war. Despite France’s Catholic faith, countries such as Sweden and France intervened to achieve their political agendas and weaken the power of the Holy Roman Empire. The war escalated into a comprehensive European conflict involving several major powers. The study included an analysis of 30 key historical documents related to the Thirty Years’ War, such as treaties, diplomatic correspondence, and history books. A descriptive-analytical approach was used to document and interpret the events of the war, its causes, and its outcomes. Documentary analysis and literature review were also used to compare different views on the causes and outcomes. The data was analyzed within a historical, religious, and political context to understand the various dimensions of the conflict. The war caused widespread destruction to major European cities, significantly impacting the economic and social structure. The Peace of Westphalia in 1648 resulted in a political and religious settlement that strengthened state sovereignty and reduced the power of the papacy, facilitating the emergence of the modern nation-state in Europe. The war also had disastrous economic and social effects, such as the destruction of agricultural land, population displacement, and increased poverty rates, which harmed population growth and economic development in the affected regions.